Peran Sekretaris dalam Meningkatkan Efisiensi Kerja di Kantor Pusat BRI - Gianti, Sri (Jurnal Utilitas, 2018)
Research intended to describe the role of secretary to enhance work efficiency of staff of Headquarters of PT Bank Rakyat Indonesia Tbk. (Persero). The research used qualitative research method. Sampling technique used was purposive sampling technique. The main informants were the secretary of marketing communication division, Marketing Division Head of Marketing Communication, and the Supervisor of Marketing Communication. The data acquired by observation, indepth interview, and document analysis. The data validated by triangulation program. The result of the research showed the secretary role to increase job efficiency by planning, saving, timming, simplifying, eradication, and gathering the work to utilize value, timing, economics of jobs, and satisfied works.